Patogenesis dan diagnosis gangguan napas saat tidur dengan Drug Induce Sleep Endoscopy (DISE) - Elvie Zulka Kautzia Rachmawati; Wresty Arief; Susyana Tamin; Rahmanofa Yunizaf; Fauziah Fardizza (Oto Rhino Laryngologica Indonesiana, 2017)
Latar belakang: Obstructive sleep apnea (OSA) ialah penyakit kronis yang terjadi akibat episode intermiten sumbatan jalan napas komplit atau sebagian saat tidur. OSA dapat menimbulkan komplikasi seperti hipertensi, diabetes melitus, stroke dan excessive daytime sleepiness yang dapat berakibat fatal. OSA merupakan bagian dari gangguan napas saat tidur. Tujuan: Mengindentifikasi letak atau level dan konfigurasi sumbatan pada saat tidur. Tinjauan pustaka: Cara untuk mendiagnosis OSA adalah nasofaringolaringoskopi dengan Muller`s maneuver, pemeriksaan polisomnography (PSG), dan drug induce sleep endoscopy (DISE). Pemeriksaan PSG merupakan standar baku emas untuk mendapakan nilai apnea-hipopnea index (AHI) yang menentukan derajat OSA. Pemeriksaan untuk mengidentifikasi lokasi sumbatan jalan napas yang menyebabkan peningkatan resistensi aliran udara adalah Muller`s maneuver dan DISE. Pada pemeriksaan DISE, digunakan propofol atau midazolam secara intravena untuk menstimulasi keadaan sumbatan pada saat tidur, dilanjutkan dengan pemeriksaan nasofaringolaringoskopi. Kesimpulan: Pemeriksaan ini merupakan cara yang sangat terpercaya untuk menentukan level sumbatan pada keadaan tidur, sehingga jenis tindakan operasi yang dilakukan menjadi lebih tepat. Kata kunci: Drug induced sleep endoscopy, midazolam, propofol, manuver Muller’s, obstructive sleep apnea, polisomnografi  ABSTRACT Background: Obstructive sleep apnea (OSA) is a common chronic disorder caused by intermittent episodes of complete or partial upper airway obstruction during sleep. It may lead to complications such as hypertension, diabetes mellitus, stroke, as well as excessive daytime sleepiness which can be fatal. OSA is a part of sleep disorder breathing. Purpose: To identify the sites or the levels of obstruction and its configuration. Literature review: Muller’s maneuver upon nasopharyngoscopy, polysomnography (PSG), and drug-induced sleep endoscopy (DISE) are the modalities for diagnosing OSA. Polysomnography is the gold standard examination for OSA, one of the variables; the apnea-hipopnea index (AHI) is used to determine the presence and severity of OSA. Muller’s maneuver and DISE are the examination to identify the sites responsible for increase in airflow resistance. DISE technique uses intravena injection of propofol or midazolam to produce obstruction in a “natural sleep” condition followed by nasopharyngolaryngoscopy examination. Conclusion: DISE is considered as a very reliable means to define the level of obstruction during sleeping, thus could help to determine appropriate surgery. Keywords: Drug induced sleep endoscopy, midazolam, propofol, Muller’s maneuver, obstructive sleep apnea, polisomnography